Former en géographie en Anthropocène : le pari d’une expérience de « repolitisation » - Sylvie Joublot-Ferré (Éducation et Socialisation)
Throughout Anthropocene, what strategies should be developed to promote the training of autonomous citizens capable of participating in public decisions? The article presents a specific device, tested in initial teacher training, at the Haute École pédagogique de Lausanne, in French-speaking Switzerland. This device articulates investigation and spatial experience, within a sensitive and participative approach. This didactic proposal is evaluated from the point of view of its ability to meet societal expectations of « politicisation » of social science teaching, particularly in geography. The epistemological as well as academic and didactic stakes are recalled. The geography of inhabiting/dwelling is particularly mobilized. The analysis of the device, in the prism of civic and political learning, is supported by several references: the legitimation of political education in the Anthropocene, critical thinking, empowerment and experience.